A profile on the spectrum of neonatal mortality and morbidity pattern of extramural neonates in the Specialised Neonatal Care Unit (SNCU) in a tertiary care hospital - D., Anuradha; S., Rajesh Kumar; A., Aravind M.; M., Jayakumar; J., J. Ganesh (International Journal of Contemporary Pediatrics, 2018)
Background: Every year, nearly four million newborn babies die in the first month of life. India carries the single largest share (around 25-30%) of neonatal deaths in the world. Neonatal deaths constitute two thirds of infant deaths in India. 45% of the deaths occur within the first two days of life. It has been estimated that about 70% of neonatal deaths could be prevented if proven interventions are implemented effectively at the appropriate time. It was further estimated that health facility-based interventions can reduce neonatal mortality by 23-50% in different settings. Facility-based newborn care, thus, has a significant potential for improving the survival of newborns in India. This research has been planned with an aim to study the profile of pattern of admissions in a SNCU and their outcomes following admission and management in the unit. Methods: All babies referred for neonatal problems (less than 28 days) and admitted in NICU will be included. Both term and preterm babies will be considered. The criteria for admission includes various causes like low birth weight, preterm, birth asphyxia, respiratory distress, hyperbilirubinemia, congenital anomalies, risk factors (maternal, neonatal, prenatal), infections and outcome will be analysed. Results: Among the 2927 admissions term babies and boys outnumbered. The common causes for admission were birth asphyxia, respiratory distress, low birthweight and preterm. Most babies had an uncomplicated stay. The mortality in the extramural neonates was due to neonatal sepsis, extreme preterm and congenital malformations. Conclusions: Intensive and interventional management, along with good neonatal monitoring and care can reduce the mortality and improve the survival of low birth weight babies and other treatable problems. Thus, a combined effort of management by pediatricians, nursing care, neonatal intensive care unit can improve the survival rates of neonates.